2001
DOI: 10.1111/1467-8411.00103
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Divide in East Asia

Abstract: The concept of a ‘digital divide’—inequality in access to modern information and communication technologies (ICTs) between industrialised and developing countries, and between urban and rural populations—has attracted much attention from policymakers, aid organisations, media and the general public. This paper places discussion of the digital divide in a broader economic context, linking it with the theory of economic growth and technological change. The network effects of diffusion of the Internet are related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…In most industries, regional attributes moderate the proximity effect. Ability to obtain knowledge (Sidorenko & Findlay, 2001) and innovate (Ritsila, 1999) varies across regions, and regions that include a wider range of capabilities, experiences, and resources are better able to incorporate external knowledge (Strambach, 2002). They become central in global structures, while less innovative regions remain peripheral.…”
Section: Regional Constraint On Networkmentioning
confidence: 99%
“…In most industries, regional attributes moderate the proximity effect. Ability to obtain knowledge (Sidorenko & Findlay, 2001) and innovate (Ritsila, 1999) varies across regions, and regions that include a wider range of capabilities, experiences, and resources are better able to incorporate external knowledge (Strambach, 2002). They become central in global structures, while less innovative regions remain peripheral.…”
Section: Regional Constraint On Networkmentioning
confidence: 99%
“…The successful diffusion and adoption of new technologies depend on the capacity of individuals to absorb the new technology, and a supportive policy environment (Sidorenko and Findlay 2001). While further investments in the information infrastructure may be required to improve overall access, what is needed now are policy measures targeted more specifically in narrowing the gap between access and usage.…”
Section: Discussionmentioning
confidence: 99%
“…1 Wong (2002) explains that "the Asian countries as a group exhibit a higher disparity in ICT diffusion than the non-Asian ones, after controlling for their level of economic development or competitiveness" (p.185). See also Sidorenko and Findlay (2001) who show differences in various IT measures (e.g. telecommunications penetration rates, and computer and Internet access) across East Asian countries.…”
Section: Digital Inequality Across Countries: the Case Of Japan Soutmentioning
confidence: 99%
“…Despite the increasing access to personal computing devices over time at both global and nationals level, there is one big inequality problem in access to, attitude towards, and the use of these devices, also known as digital divide, a term that was first coined in late 20 th century and has been well researched topic ever since [16,[19][20]. Some studies confirmed the existence of digital divide between race, age, and gender [3,7] while some other argue that income or socioeconomic status (SES) is the most important factor of digital divide [1][2].…”
Section: Literature Reviewmentioning
confidence: 99%